Implications of World Health Organization classification for body mass index on the correlations between common electrocardiographic indexes for left ventricular hypertrophy and left ventricular mass. (16th November 2016) - Kurisu, Satoshi; Ikenaga, Hiroki; Watanabe, Noriaki; Higaki, Tadanao; Shimonaga, Takashi; Ishibashi, Ken; Dohi, Yoshihiro; Fukuda, Yukihiro; Kihara, Yasuki
ABSTRACT: Background : Some electrocardiographic indexes such as Cornell index, Cornell product index, or Sokolow–Lyon index remain to be used in the clinical setting. We assessed the effects of body mass index (BMI) on the correlations between these ECG indexes and left ventricular mass (LVM). Methods : One hundred ninety-six outpatients who underwent both ECG and echocardiography on the same day were included in this study. In accordance with the World Health Organization (WHO) classification of BMI, the patients were classified into the four groups: underweight (<18.5 kg/m 2, n = 30), normal weight (18.5–24.9 kg/m 2, n = 83), overweight (25–29.9 kg/m 2, n = 43), and obese (≥30 kg/m 2, n = 40). Results : With increasing WHO classification of BMI, Cornell index (RaVL+SV3), Cornell product index [(RaVL+SV3)RQRS duration], and LVM increased. On the other hand, Sokolow–Lyon index (SV1+RV5) decreased. Cornell index correlated with LVM in normal weight group ( r = 0.27, p = 0.015), but did not in the other groups. Cornell product index also correlated with LVM in normal weight group ( r = 0.30, p = 0.006), but did not in the other groups. Sokolow–Lyon index correlated with LVM well in normal weight group ( r = 0.32, p = 0.004) and better in underweight group ( r = 0.61, p = 0.0004). However, no correlations were found in overweight and obese groups. Conclusions : Our results suggest that BMI influences the correlations between these ECG indexes and LVM, and should be taken into consideration when assessing LVH.